2007
DOI: 10.3354/dao01846
|View full text |Cite
|
Sign up to set email alerts
|

Severe mortality in wild Atlantic salmon Salmo salar due to proliferative kidney disease (PKD) caused by Tetracapsuloides bryosalmonae (Myxozoa)

Abstract: Extensive mortality in Atlantic salmon fry was reported in the River Åelva from 2002 to 2004. Dead fish were collected in late summer 2006, and live fish were sampled by electrofishing in September the same year. At autopsy and in histological sections, the fish kidneys were found to be pale and considerably enlarged. Proliferative lesions with characteristic PKX cells were seen in a majority of the fish. DNA from kidney samples of diseased fish was subjected to PCR and sequencing, and the amplified sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 17 publications
5
113
0
1
Order By: Relevance
“…In Switzerland, it has been suggested that recent decreases in brown trout populations were caused by PKD (Wahli et al 2002(Wahli et al , 2007. A similar scenario is thought to be the case for Atlantic salmon in Norway (Sterud et al 2007), and (Kristmundsson et al 2010) hypothesize that PKD may play a significant role in the recent decline in Arctic charr populations in Iceland. Indeed, there is justification for concluding that PKD is an important factor for these declines in trout populations, and it is to be expected that the consequences of PKD will become more severe if water temperatures are to increase in the future (Burkhardt-Holm & Scheurer 2007, Okamura et al 2011.…”
Section: Effects Of Pkd In Wild Fishesmentioning
confidence: 93%
See 3 more Smart Citations
“…In Switzerland, it has been suggested that recent decreases in brown trout populations were caused by PKD (Wahli et al 2002(Wahli et al , 2007. A similar scenario is thought to be the case for Atlantic salmon in Norway (Sterud et al 2007), and (Kristmundsson et al 2010) hypothesize that PKD may play a significant role in the recent decline in Arctic charr populations in Iceland. Indeed, there is justification for concluding that PKD is an important factor for these declines in trout populations, and it is to be expected that the consequences of PKD will become more severe if water temperatures are to increase in the future (Burkhardt-Holm & Scheurer 2007, Okamura et al 2011.…”
Section: Effects Of Pkd In Wild Fishesmentioning
confidence: 93%
“…Yet, the impact of PKD on wild fish is a matter of some uncertainty because the effect of PKD on wild fish populations has not been adequately documented. At some European localities, it has been concluded that PKD is responsible for high mortality in wild brown trout Salmo trutta (Wahli et al 2002(Wahli et al , 2007 and Atlantic salmon S. salar (Sterud et al 2007). Even though this is probable, it is difficult, however, to prove with certainty that PKD is the only cause of the observed mortalities.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…There is a growing body of evidence indicating that some pathogens become more prevalent (Chiaramonte, Munson, & Trushenski, 2016; Sterud et al., 2007) and more virulent at warmer temperatures (Smith et al., 2014). For example, it has been shown that increased expression of virulence factors is correlated with increased temperature in Vibrio species (Mahoney, Gerding, Jones, & Whistler, 2010; Oh, Lee, Lee, & Choi, 2009).…”
Section: Discussionmentioning
confidence: 99%